(untitled) (Heritage, 2025)
The renowned Serbian writer Desanka Maksimović (1898–1993) translated into Serbian mainly Russian poets, followed by Armenian, Georgian, Ukrainian, and other Soviet poets. Among her numerous translations, there are also two poems by Belarusian poets: “Who Goes There?” by Yanka Kupala and “Where to Begin?” by Yevdokiya Los, both translated from Russian. The study presented to the academic and professional public arises from the need to explain the connections between Desanka Maksimović and Belarusian literature, clarify misinterpretations, and realistically depict her role in developing Belarusian-Serbian literary relations. Her connections with Russian writers are also presented for better comparison and causal analysis.